Spot 42 RNA of Escherichia coli is not an mRNA. - Rice, P W (1987)
Spot 42 RNA of Escherichia coli, a 109-nucleotide RNA that influences the level of DNA polymerase I, has an AUG triplet preceded by a purine-rich potential ribosome-binding site and is followed by a short (14-triplet) potential open reading frame. Although the RNA bound to ribosomes, it did so inefficiently and nonproductively. When fused to lacZ sequences, spot RNA did not support the synthesis of beta-galactosidase. Also, the biological effects of spot 42 RNA were not altered by mutation of the tyrosine UAU codon to the chain termination UAG. We conclude that the effects of spot 42 RNA are mediated by the RNA itself and not by a spot 42 RNA-encoded peptide.